Perancangan Modular Indoor Booth untuk Produk Pakaian, Sepatu dan Makanan - Lisa Agustin; Yusita Kusumarini; filipus priyo suprobo (Intra, 2014)
Modular indoor booth design is an inovation on product display system for the interior of exhibition space. The aim of this booth design is to facilitate the exhibition’s organizer in setting up and disassembling the booth. Combining modular system and breakdown system in the design may provide an ease in many aspects, such as in transportation, assembly dan storage. Methodology design by Kembel[1] used in the design process, including 5 stages consist of understand, define, ideate, prototype and test. The advantages of this display system are its capability in adapting on different situation may appear in exhibition space and creating several different forms from one set booth design. It also supports the world in overcome global warming by using material efficiently.